Incidencia de las clases de educación física en el desarrollo de la lateralidad en niños y niñas de 4-5 años de la Escuela de Educación Básica Juan Javier Espinoza, del Recinto Resbalón, del Cantón Baba, año 2022 - Dulcey Andino, Carlos Duver (2022)
The purpose of this research was to analyze the incidence of sensory integration in the development of motor coordination in players of the sub-10 category of the "Soccer Babahoyo" football school, in the Babahoyo Canton. Methodology used: A research with a mixed approach, descriptive-correlational type and with a non-experimental cross-sectional design was developed; in which an intentional sample of fifteen children was selected, representing 100% of the sample. The "3JS" test was applied to evaluate seven fundamental aspects related to motor coordination. General dynamics (jumping, turning and moving) and visuomotor coordination (throwing, hitting, dribbling and driving). Results obtained: It was found that approximately 73.56% of the players in the su-10 category of the "Soccer Babahoyo" training football school, presenting "regular" motor coordination when finding deficiencies in the execution of the tests before mentioned. Likewise, it has been possible to identify present deficiencies in terms of the planning and methodologies used by the coaches. Proposal: A plan of sensory activities based on the modified game is proposed to develop motor coordination in the players of the sub-10 category of the "Soccer Babahoyo" football school, in the Babahoyo Canton, Los Ríos Province.